Implementation of a YBCO Superconducting ZFC-Magnetic Bearing Prototype - Arsénio, António (2020)
This paper presents the conception and real prototype implementation of an original superconducting frictionless zero field cooling (ZFC) bearing. In the previous paper, a viability study of a ZFC-superconducting bearing concept was conducted. It showed that the virtual prototype was feasible. Moreover, the simulation studies showed that a ZFC superconducting track provides not only effective lateral stability but also higher levitation forces than the commonly used field cooling (FC) tracks. In this paper, the new ZFC bearing virtual prototype is modeled in three-dimensional and physically realized. The implementation was made in high-density polyurethane, for low-temperature robustness, using both a three axes computer numerical control (CNC) milling machine and an additive manufacturing technique. Results show the effectiveness of the real bearing. Static analysis was done and dynamic analysis was also introduced.